Pharmacokinetic modeling of over-the-counter drug diphenhydramine self-administered in overdoses in Japanese patients admitted to hospital - Koichiro Adachi; Satoru Beppu; Mariko Terashima; Wataru Kobari; Makiko Shimizu; Hiroshi Yamazaki (BMC, 2021)
Abstract Background Although the over-the-counter H1 receptor antagonist diphenhydramine is not a common drug of abuse, it was recently recognized as one of the substances causing acute poisoning in patients attempting suicide that led to admissions to our hospital emergency room. Case presentation Two patients [women aged 21 and 27 years (cases 1 and 2)] were emergently admitted after intentionally taking overdoses of 900 and 1200 mg diphenhydramine, respectively. The plasma diphenhydramine concentrations in case 1 were 977 and 425 ng/mL at 2.5 and 11.5 h after single oral overdose, and those in case 2 were 1320 and 475 ng/mL at 3 and 18 h after administration, respectively. We set up a simplified physiologically based pharmacokinetic (PBPK) model that was established using the reported pharmacokinetic data for a microdose of diphenhydramine. The two virtual plasma concentrations and the area under the curve (AUC) values extrapolated using the PBPK model were consistent with the observed overdose data. This finding implied linearity of pharmacokinetics over a wide dosage range for diphenhydramine. Conclusions The determined plasma concentrations of diphenhydramine of around 1000 ng/mL at ~ 3 h after orally administered overdoses in cases 1 and 2 may not have been high enough to cause hepatic impairment because levels of aspartate aminotransferase and alanine aminotransferase were normal; however, there was an increase in total bilirubin in case 1. Nonetheless, high virtual liver exposures of diphenhydramine were estimated by the current PBPK model. The present results based on drug monitoring data and pharmacokinetic predictions could serve as a useful guide when setting the duration of treatment in cases of diphenhydramine overdose.